2017
DOI: 10.1039/c7ib00018a
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of heterogeneous wound tissue samples into relative macrophage phenotype compositionviamodels based on gene expression

Abstract: Macrophages, the primary cell of the innate immune system, act on a spectrum of phenotypes that correspond to diverse functions. Dysregulation of macrophage phenotype is associated with many diseases. In particular, defective transition from pro-inflammatory (M1) to anti-inflammatory (M2) behavior has been implicated as a potential source of sustained inflammation that prevents healing of chronic wounds such as diabetic ulcers. In order to design effective treatments, an understanding of the relative presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…In our experiments, we found that macrophage-specific inhibition of WNT secretion resulted in a significant reduction in ALDH + enrichment in hetero-spheroids, implying that WNT signaling was likely involved bi-directionally in CSC/macrophage interactions. The lone WNT ligand we found significantly upregulated in M2-like macrophages (compared to monocytes or M0 macrophages) was WNT5B , in line with transcriptomic and gene expression analyses performed on human M2 macrophages by other groups [41, 42]. Interestingly, macrophage WNT5B knockdown resulted in the loss of ALDH + enrichment in the CSC compartment of hetero-spheroids, with an associated loss of IL-6 secretion.…”
Section: Discussionsupporting
confidence: 86%
“…In our experiments, we found that macrophage-specific inhibition of WNT secretion resulted in a significant reduction in ALDH + enrichment in hetero-spheroids, implying that WNT signaling was likely involved bi-directionally in CSC/macrophage interactions. The lone WNT ligand we found significantly upregulated in M2-like macrophages (compared to monocytes or M0 macrophages) was WNT5B , in line with transcriptomic and gene expression analyses performed on human M2 macrophages by other groups [41, 42]. Interestingly, macrophage WNT5B knockdown resulted in the loss of ALDH + enrichment in the CSC compartment of hetero-spheroids, with an associated loss of IL-6 secretion.…”
Section: Discussionsupporting
confidence: 86%
“…Second, macrophages are highly plastic, and their phenotypic change may lead to entirely different immune responses against the implants. Third, recent studies are increasingly uncovering the essential, underestimated roles of macrophages (and their precursor, monocytes) in tissue regeneration and particularly bone development and repair [ 16 , 17 ]. They can not only eliminate debris and regulate bone resorption but, more importantly, act as a powerhouse to secrete an array of cytokines under dynamical control.…”
Section: Introduction: Modulating But Not Resisting Macrophages At mentioning
confidence: 99%
“…In contrast, M2c macrophages clear apoptotic cell debris and secrete enzymes that remodel the extracellular matrix, while M2a macrophages produce growth factors that stimulate granulation tissue formation . Notably, a timely transition from M1 to M2a is essential for successful wound healing, and dysregulation of macrophage activation is associated with chronic wounds . The timing of M2c activation has not been well characterized, but studies suggest that this phenotype acts at early stages of wound healing …”
Section: Introductionmentioning
confidence: 99%
“…8 Notably, a timely transition from M1 to M2a is essential for successful wound healing, and dysregulation of macrophage activation is associated with chronic wounds. [9][10][11][12][13] The timing of M2c activation has not been well characterized, but studies suggest that this phenotype acts at early stages of wound healing. 7 One potential mechanism behind dysfunctional macrophage behavior in DFUs is the interaction of macrophages with the colonizing microbiota.…”
Section: Introductionmentioning
confidence: 99%